Perancangan Absensi Berbasis Web Dengan Metode Waterfall (Studi Kasus: PT. GlobalRiau Data Solusi) - Rizka Hafsari; Aryanto; Rendy Rahmadani Saputra; Muhammad Afin Wirdyansah (Universitas Muhammadiyah Riau, 2023)
Employee attendance is an important activity for the company because it can affect the amount of revenue. In implementing the recording procedure, this attendance requires accuracy in order to produce a good attendance report. PT GlobalRiau Data Solution (GDS) is a company or industry that provides Internet connections and other related services. GDS has a communication infrastructure connected to the Internet, where GDS then shares its network connection capacity with customers who need network connection services. Previously, attendance at PT.GDS was carried out manually within the company, but this manual process had many obstacles, including manipulation of attendance even with ineffective data storage. Therefore, the research aims to design a website-based attendance system or attendance recording using the waterfall method so that it can improve the attendance process to be more efficient. Web technology is used because it offers advantages, such as being able to work on any system as long as there is an internet connection and does not require a computer with a high capacity to run a web application while the use of the waterfall method is applied sequentially and systematically. The waterfall method begins design to maintenance and is implemented in stages.